Kajian Efektmtas Dan Efisiensi Proses Perizinan Perpotongan Dan Persinggungan Jalur Kereta Api Dengan Bangunan Lain - Purwoko, Purwoko; Subaryata, Subaryata (Warta Penelitian Perhubungan, 2011)
Act No. 23 of 2007 on the Railways, in Article 91 paragraph (1) mandates that the intersection between the rail and roads made no plot. Exceptions to the provisions referred to in paragraph (1) can only be done while ensuring safety and smooth running train rides and road traffic. I71e study tries to review the drafting of the concept of the licensing process the intersection and railroad intersection with another building of effective and efficient, and recommendations for improvements of licensing. As a tool used for analysis is a method Analytical Hierarchy Process (AHP), with secondary data collection in related institutions and primary data collection through questionnaires to the experts as respondents in the field of railway infrastructure in some instances. I71e results obtained from the study indicate the priority that need attention include reducing the processing time, one-stop, telecommunications, information communication, shorten theprocess and delegation of authority, determination. To improve the licensing process effective and efficient need to change the five scale.Keywords: Effectiveness, Efficiency, Licensing Process